The Analysis of Students’ Critical Thinking and Scientific Literacy Skills - Zuhra, Fatma; Nurhayati, Nurhayati; Arifiyanti, Fitria (Indonesian Review of Physics (IRiP), 2021)
This research aimed to determine critical thinking and scientific literacy skills for the tenth-grade students of Bireuen Public High School 2 (SMAN 2 Bireuen). This research used a quantitative approach with a descriptive research design. There were 27 tenth-grade students of the second science class who selected samples through the purposive sampling technique. Descriptive analysis is a research type that does not provide the treatment, manipulation, or modification on the independent variables, but it describes an actual condition. The instrument used in this research was a test adapted from PISA questions. The results showed that the critical thinking and scientific literacy skills of tenth-grade students of SMAN 2 Bireuen were in the fair category. Therefore, it is necessary to apply learning approaches/models that can train students’ scientific literacy skills to get used to carrying out scientific activities, solving scientific problems, providing explanations for a phenomenon scientifically, and using scientific evidence to explain a fact.